Synergistic cross‐talk of hedgehog and interleukin‐6 signaling drives growth of basal cell carcinoma. Issue 11 (1st October 2018) - Sternberg, Christina; Gruber, Wolfgang; Eberl, Markus; Tesanovic, Suzana; Stadler, Manuela; Elmer, Dominik P.; Schlederer, Michaela; Grund, Sandra; Roos, Simone; Wolff, Florian; Kaur, Supreet; Mangelberger, Doris; et al.
Abstract : Persistent activation of hedgehog (HH)/GLI signaling accounts for the development of basal cell carcinoma (BCC), a very frequent nonmelanoma skin cancer with rising incidence. Targeting HH/GLI signaling by approved pathway inhibitors can provide significant therapeutic benefit to BCC patients. However, limited response rates, development of drug resistance, and severe side effects of HH pathway inhibitors call for improved treatment strategies such as rational combination therapies simultaneously inhibiting HH/GLI and cooperative signals promoting the oncogenic activity of HH/GLI. In this study, we identified the interleukin‐6 (IL6) pathway as a novel synergistic signal promoting oncogenic HH/GLI via STAT3 activation. Mechanistically, we provide evidence that signal integration of IL6 and HH/GLI occurs at the level of cis‐ regulatory sequences by co‐binding of GLI and STAT3 to common HH‐IL6 target gene promoters. Genetic inactivation of Il6 signaling in a mouse model of BCC significantly reduced in vivo tumor growth by interfering with HH/GLI‐driven BCC proliferation. Our genetic and pharmacologic data suggest that combinatorial HH‐IL6 pathway blockade is a promising approach to efficiently arrest cancer growth in BCC patients. Abstract : What's new? Persistent activation of hedgehog (HH)/GLI signaling represents the main driver signal for the development of basal cell carcinoma (BCC), a common non‐melanoma skin cancer with rising incidence. Small molecule hedgehog pathway inhibitors are successfully used for the treatment of hedgehog‐driven BCC, but frequent drug resistance calls for improved strategies. Here, the authors identified the interleukin‐6 pathway as a novel synergistic signal promoting oncogenic HH/GLI via STAT3 activation. The synergistic interaction was required for the in vivo growth of hedgehog‐driven BCC. The study thus provides a rationale for effective combination treatments simultaneously targeting oncogenic hedgehog and interleukin‐6 signaling in BCC patients.